Fate of hopane biomarkers during in-situ burning of crude oil — A laboratory-scale study. (August 2018) - John, Gerald F.; Han, Yuling; Clement, T. Prabhakar
Abstract: In-situ burning (ISB) is a remediation strategy that is used for managing oil spills. ISB generates heavy residues that can submerge and negatively impact benthic environments. To track the fate of toxic contaminants in ISB residues, a conservative hopane biomarker, such as C30 -αβ hopane, is often used. Furthermore, diagnostic ratios of various hopanes are used for source oil identification. Use of these biomarkers assume that during ISB the quantity of C30 -αβ hopane will be conserved, and the diagnostic ratios of various hopanes will be stable. The objective of this study is to test the validity of these two assumptions. We conducted laboratory-scale ISB experiments using a model oil prepared from commercial C30 -αβ hopane standard, and a reference crude oil. Laboratory data collected under controlled burning conditions show that C30 -αβ hopane will not be conserved; however, the diagnostic ratios of hopanes will still remain fairly stable. Graphical abstract: Unlabelled Image Highlights: In-situ burning (ISB) is one of the commonly used oil spill mitigation techniques. It is assumed that C30 -αβ hopane will be conserved during ISB. Our laboratory results show that C30 -αβ hopane will not be conserved during ISB. However, diagnostic ratios of hopanes used for chemical fingerprinting will remain stable.